A month with the master : postillations of His Holiness Satguru Baba Gurbachan Singh Ji - Singh, Gurbachan, 1930- (Sant Nirankari Mandal, 1972)
Discourses, from December 25, 1969 to January 22, 1970, by the head of the Sant Nirankari Mission, an eclectical and non-traditional religious organization in India.